Orthodontic management of bilateral maxillary canine-first premolar transposition and bilateral agenesis of maxillary lateral incisors: a case report - Elena Di Palma; Biagio Di Giuseppe; Michele Tepedino; Claudio Chimenti (Dental Press Editora, 2015)
INTRODUCTION: Maxillary canine-first premolar transposition (Mx.C.P1) is an uncommon dental positional anomaly that may create many orthodontic problems from both esthetic and functional points of view. OBJECTIVE: In this report we show the orthodontic management of a case of Mx.C.P1 associated with bilateral maxillary lateral incisor agenesis and unilateral mandibular second premolar agenesis METHODS: The patient was treated with a multibracket appliance and the extraction of the lower premolar. RESULTS: treatment was completed without the need for any prosthetic replacement.